2019
DOI: 10.1155/2019/3737083
|View full text |Cite
|
Sign up to set email alerts
|

Anemia, Blood Transfusion, and Filter Life Span in Critically Ill Patients Requiring Continuous Renal Replacement Therapy for Acute Kidney Injury: A Case-Control Study

Abstract: Background. Filter clotting is frequent during continuous renal replacement therapy (CRRT), which increases anemia risk. We studied anemia and blood transfusion in critically ill patients requiring CRRT for acute kidney injury and assessed the relationship between CRRT filter life span and PRBC transfusion. Methods. A case-control study was conducted at a tertiary-care intensive care unit (ICU) where CRRT cases were matched with controls for age, gender, admission category, and severity of illness. Daily hemog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…A study published by Al-Dorzi et al showed that CRRT use among ICU patients is inevitably linked with a larger decline in hemoglobin levels, requiring red blood cell transfusion [26]. This association has also been identified in our critically ill patients.…”
Section: Discussionsupporting
confidence: 68%
“…A study published by Al-Dorzi et al showed that CRRT use among ICU patients is inevitably linked with a larger decline in hemoglobin levels, requiring red blood cell transfusion [26]. This association has also been identified in our critically ill patients.…”
Section: Discussionsupporting
confidence: 68%
“…Patients in the CytoSorb group experienced a significant decrease in hemoglobin levels, while patients in the MARS group did not. As this decrease was observed over a median period of more than 72 h, we cannot assess if it is due to erythrocyte entrapment or destruction within the CytoSorb/CRRT filter as demonstrated by Al-Dorzi et al [ 44 ] or to critical illness and the frequent blood withdrawal in the ICU [ 45 ]. A decrease in platelet count was observed for both MARS and CytoSorb groups.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, critically ill patients with acute kidney injury (AKI) are at a higher risk of developing anemia due to both kidney dysfunction and the severity of their illness. Renal replacement therapy, including continuous renal replacement therapy (CRRT), can further exacerbate anemia because of blood loss from hemofilter clotting that cannot be returned 13 as well as bleeding associated with catheters or anticoagulation 14 .…”
Section: Introductionmentioning
confidence: 99%